Local Economic Transformation Through International Collaboration: Optimizing the Creative Economic Potential of Edelweiss Flowers Based On Sharia Principles - Ismawati; Hanim Misbah; Nuur Halimatus Saadiah Masrukhin; Atina Hidayati; Mitra Sami Gultom; Dewi Maharani; Inarotul A'yun; Andi Bahri S; Hastin Tri Utami; Puspita; Alip Toto Handoko (Yayasan Darussalam Patalassang, 2026)
Non-Indexed Publication